Antineuroinflammatory Properties of Compounds from Ethyl Acetate Fraction of Marsilea crenata C. Presl. Against Toll-Like Receptor 2 (3A7B) In Silico - Ma’arif, Burhan; Samudra, Reyhan Rahma; Muslikh, Faisal Akhmal; Dewi, Tanaya Jati Dharma; Muchlasi, Luthfi Ahmad (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 2 (2022): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2022)
Parkinson's disease (PD) can be triggered by overactive TLR2 due to α-synuclein abnormalities and aggregation. Marsilea crenata C. Presl. leaves inhibit neuroinflammatory progression. This study aimed to predict the antineuroinflammatory activity of M. crenata leaves with TLR2 (ID 3A7B) in an in silico study. The list of chemicals was collected through metabolite profiling with UPLC-QToF MS/MS, then analyzed for physicochemical properties using SwissADME and toxicity using the ProTox II online program. This analysis confirmed the molecule's safety for therapeutic use. ChemDraw 12.0 was used to build metabolite-profiled compounds. Avogadro 1.2.0 was utilized to optimize geometry, while PyRx 0.8 was used for Autodock Vina molecular docking. Agonist-TLR2 interactions were examined using docking results from Biovia Discovery Studio 2021. Tethering is valid; the program can be used because the RMSD is less than 2. The results showed that 6 of the 84 metabolite-profiled compounds were antagonistic to 3A7B and shared similar pharmacophore distances and amino acid linkages with N-acetyl-D-glucosamine, a native ligand of 3A7B. By binding to TLR2, the compounds from the ethyl acetate fraction of M. crenata leaves may potentially inhibit PD progression.